PERAN KEPEMIMPINAN KYAI DALAM MEMBENTUK KARAKTER SANTRI DI PONDOK PESANTREN AL-MASHDUQIAH PATOKAN KRAKSAAN PROBOLINGGO - malikul habsi (STAI Ma'had Aly Al-Hikam Malang, 2022)
Islamic boarding school is an Islamic institution that has a noble purpose, in which there are elements of the cottage, one of which is called santri. To become students who are useful and can play an active role in society, character education is needed when living life in Islamic boarding schools, In Islamic boarding schools, a leader figure is needed who can provide examples and role models for students. KH. Mukhlisin Sa'ad. is a figure who is compassionate and patient in educating the character of students, so that many of the students or alumni greatly admire him. The method used in this study is a qualitative method in which the source of the results is obtained from the results of interviews with predetermined sources. The results of the study prove that the leadership role of the kyai is very urgent for the life of the Islamic boarding school community, especially the students at the AlI islamic Boarding School Mashduqiah. Keywords:Leadership of Kyai, Character of Santri.